2015
DOI: 10.1128/genomea.01585-14
|View full text |Cite
|
Sign up to set email alerts
|

Draft Genome Sequences of Six Actinobacillus pleuropneumoniae Serotype 8 Brazilian Clinical Isolates: Insight into New Applications

Abstract: Actinobacillus pleuropneumoniae is the causative agent of swine pleuropneumonia, a highly contagious disease associated with pigs of all ages that results in severe economic losses to the industry. Here, we report for the first time six genome sequences of A. pleuropneumoniae clinical isolates of serotype 8, found worldwide.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 8 publications
0
11
0
Order By: Relevance
“…pleuropneumoniae Serotype 8. The set of clusters of the coding DNA sequences (CDS) predicted for A. pleuropneumoniae serotype 8 was based on the seven genomes of clinical isolates taken from pig farms, six from Brazil [21] and one from the United Kingdom [22]. In this analysis, the CD-HIT v.4.6.1 program [24,25] was used to consider an identity threshold of 0.85 to cluster the CDS.…”
Section: Determination Of Protein-coding Sequence Set In Amentioning
confidence: 99%
See 2 more Smart Citations
“…pleuropneumoniae Serotype 8. The set of clusters of the coding DNA sequences (CDS) predicted for A. pleuropneumoniae serotype 8 was based on the seven genomes of clinical isolates taken from pig farms, six from Brazil [21] and one from the United Kingdom [22]. In this analysis, the CD-HIT v.4.6.1 program [24,25] was used to consider an identity threshold of 0.85 to cluster the CDS.…”
Section: Determination Of Protein-coding Sequence Set In Amentioning
confidence: 99%
“…Over the years, A. pleuropneumoniae serotype 8 has been neglected in identification studies due to failures in serotyping techniques, and as a result, genomic studies involving this serotype are nonexistent. Although recent studies have showed a wide distribution of this serotype in several regions, such as the United Kingdom [17,18], North America [19], and Brazil [20], just recently A. pleuropneumoniae serotype 8 genome sequence was available [21,22].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The sequences of the final sRNA candidates were also searched by BLASTn in the other 11 serotype reference genomes available of A. pleuropneumoniae and in the genomes of six Brazilian clinical isolates (Pereira et al 2015a) to investigate their distribution among the species. In addition, 33 genomes of 14 other Pasteurellaceae species, whose complete genomes are available from Genbank, were also searched (Supplemental Table S4).…”
Section: In Silico Identification Of Srnasmentioning
confidence: 99%
“…A further 14.5% of the tested isolates had tet (B) genes that appeared to be associated with plasmid sequences ( Bossé et al, 2017 ). Wgs for six Brazilian isolates also indicate the presence of tet (B) associated with plasmid sequences in four of these isolates ( Pereira et al, 2015 ). As small plasmids often appear to be common amongst members of the Pasteurellaceae ( Michael et al, 2018 ), the aim of this study was to identify the tet (B) plasmids present in these sequenced isolates of A. pleuropneumoniae .…”
Section: Introductionmentioning
confidence: 99%